Multi-criteria analysis of the feasibility of e-waste pre-treatment units in a Brazilian city - da Silva Sales, Ingrid Jale [UNESP] (2024)
Waste electrical and electronic equipment (WEEE) has been largely generated in Brazil and worldwide. Besides the interest in recovering their valuable materials, some contain potentially hazardous components that must be removed and destined for treatment. WEEE pre-treatment is a critical step to efficiently sort and recover such components, but data availability is scarce in Brazil and developing countries, what may hinder feasibility analyses for its wider implementation. There is an increasing demand for studies that analyse the feasibility of WEEE reverse logistics systems, supporting their optimization. The present study analysed the feasibility of implementing WEEE pre-treatment units in a Brazilian municipality based on different levels of WEEE disassembly (A—basic; B—intermediate; and C—advanced) and implementation scenarios. Using the StEP tool and the multicriteria method ELECTRE TRI, the study classified implementation alternatives into three categories: more feasible; intermediate; and less feasible. The most feasible scenarios were related to an intermediate disassembly level (B). Alternatives with at least two pre-treatment units within the city were more feasible, even after some sensitivity analyses, indicating the advantages of smaller units and lower transport distances. The methodology and results may be applicable to other cities, both in Brazil and in other countries.